Frontiersmen : warfare in Africa since 1950 - Clayton, Anthony, 1928- (Warfare and history., 1999)
Since 1950 there has been almost continuous military unrest in Africa. This study discusses the view that warfare in North Africa has been mainly a matter of identity, while sub-Saharan warfare is comparable with that of precolonial Africa.